Safe school from bullying through environmental design in secondary school / Azna Abdul Wahab - Abdul Wahab, Azna (2020)
Research into the subject of bullying was unfailingly able to identify general locations where bullying incidents tend to occur. However, it is also crucial to study the physical environment in the area which is believed to be able to influence the crime to occur. A mixed method approach was used in this case study by using questionnaire and field observation as the data collection method. The site selection for the present study was based on the highest number of perpetrations between the age 7 to 18 years. Four secondary schools from Selangor were chosen in this case study. Random sampling was applied in selecting the samples. The survey response rate for this study was 84.53%. The findings suggest that there can be a potential relationship between bullying possibility and physical environment. The bullying can occur in a classroom when the teacher is absent, toilets, and canteens. The possibility of bullying to occur can be diffusing from one location to another location due to the students’ behaviour in spending their recess time. Thus, the physical environment in certain area plays an important role in providing them a sense of comfort and safety.